Ecological generalism facilitates the evolution of sociality in snapping shrimps. (4th October 2017) - Brooks, Katherine C.; Maia, Rafael; Duffy, J. Emmett; Hultgren, Kristin M.; Rubenstein, Dustin R.
Abstract: Evidence from insects and vertebrates suggests that cooperation may have enabled species to expand their niches, becoming ecological generalists and dominating the ecosystems in which they occur. Consistent with this idea, eusocial species of sponge‐dwelling Synalpheus shrimps from Belize are ecological generalists with a broader host breadth and higher abundance than non‐eusocial species. We evaluate whether sociality promotes ecological generalism (social conquest hypothesis) or whether ecological generalism facilitates the transition to sociality (social transition hypothesis) in 38 Synalpheus shrimp species. We find that sociality evolves primarily from host generalists, and almost exclusively so for transitions to eusociality. Additionally, sponge volume is more important for explaining social transitions towards communal breeding than to eusociality, suggesting that different ecological factors may influence the independent evolutionary origins of sociality in Synalpheus shrimps. Ultimately, our results are consistent with the social transition hypothesis and the idea that ecological generalism facilitates the transition to sociality.